2019
DOI: 10.1097/nmc.0000000000000518
|View full text |Cite
|
Sign up to set email alerts
|

Chinese American Women's Experiences with Postpartum Depressive Symptoms and Mental Health Help-Seeking Behaviors

Abstract: Callouts: 1) Chinese American women may first disclose depressive symptoms to their spouses and that they could rely on them for emotional and instrumental support. 2) Practicing postpartum traditions out of respect for older family members is common among Chinese American women, even if they do not necessarily believe in them. 3) For Chinese American women, barriers to help-seeking include mental health care costs, lack of services or not knowing where the services are, stigma, and language/cultural barriers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 30 publications
1
37
1
Order By: Relevance
“…This low level of perceived need could be explained by low levels of knowledge and awareness with regard to the importance of mental health problems [54,55]. Studies on perinatal Chinese American women have revealed that several women believe that postpartum depression does not exist in China [56]. Furthermore, the somatization of mental illness has been commonly reported in China [57].…”
Section: Principal Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This low level of perceived need could be explained by low levels of knowledge and awareness with regard to the importance of mental health problems [54,55]. Studies on perinatal Chinese American women have revealed that several women believe that postpartum depression does not exist in China [56]. Furthermore, the somatization of mental illness has been commonly reported in China [57].…”
Section: Principal Findingsmentioning
confidence: 99%
“…If pregnant women's psychological distress appeared in the form of somatic symptoms, they may be more likely to seek medical help. Pregnant women might also tend to view a disturbed mood as a normal part of pregnancy [27,56], thereby resulting in the underreporting of the need to seek help.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Noted in 10 of the 18 studies, this obstacle manifested in various ways ranging from socioeconomic restrictions such as lack of financial or insurance coverage to structural inequalities such as a lack of mental health infrastructure in their area [ 1 , 16 , 25 , 26 ]. Cultural competence was a critical factor as participants expressed concerns about the lack of mental health professionals who are both culturally and linguistically capable [ 14 , 18 , 19 , 21 , 25 , 37 ].…”
Section: Reviewmentioning
confidence: 99%
“…Of the 18 studies, 15 cited prejudice or stigma as the primary reason in avoiding treatment, which was, by far, the most prevalent barrier among Henderson’s four barriers. On further elaboration, participants mentioned the fear of being perceived as crazy, saving “face”, and fear of bringing shame to their family as common themes [ 1 , 3 , 13 , 14 , 16 , 18 , 21 , 25 , 26 ]. In seven of the 18 studies, mental illness was attributed to personal incompetence or weakness, in which those suffering did not have the mental fortitude or resilience to cope with their own problems [ 4 , 25 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation